On emergencies and emigration: how (not) to justify compulsory medical service. Issue 8 (20th April 2016) - Blake, Michael
Abstract : I have argued that the best way to understand the supposed right to restrict emigration is with reference to the concept of an emergency; restrictions on emigration are permitted, if at all, only as responses to an emergency situation, and must be judged with reference to the ethics of responding to such an emergency. Eszter Kollar argues, against this, that the concept of 'emergency' fails to describe the actual situation in low/middle-income countries, in which shortages of medical personnel are long-standing problems; she also argues that there is no need to invoke the concept of an emergency, when we might simply discuss these restrictions with reference to the relative importance of the human goods and interests involved. I argue, against Kollar, that we have no reason to think that an emergency must involve novelty; if the moral stakes are significant enough, we have reason to think of a situation as an emergency, regardless of when that situation began. I argue, too, that we have reason to differentiate between restrictions of liberties undertaken as part of the process of specifying liberal freedoms and emergency restrictions of those liberties defended by liberalism itself. The latter, I suggest, ought to be recognised and defended as a distinct moral category, if only to recognise the continuing moral remainder when a liberal right is temporarily suspended under emergency circumstances. I conclude that a permission to restrict emigration is, if at all, only justifiable as an emergency response to unfavourable circumstances, and ought not to be analysed in the more conventional liberal terms Kollar deploys.